Risk factors for neonatal mortality prior to hospital discharge in brachycephalic and nonbrachycephalic dogs undergoing cesarean section. Issue 7 (10th August 2022) - Adams, Daniel J.; Ellerbrock, Robyn E.; Wallace, Mandy L.; Schmiedt, Chad W.; Sutherland, Brian J.; Grimes, Janet A.
Abstract: Objectives: To compare neonatal survival to discharge rates between brachycephalic and nonbrachycephalic dogs undergoing cesarean section (c‐section) and identify risk factors for neonatal mortality. Study design: Retrospective study. Animals or sample population: A total of 480 puppies from 90 bitches undergoing 106 c‐sections. Methods: Medical records of c‐sections performed between January 2012 and September 2021 were reviewed. Data collected included brachycephalic versus nonbrachycephalic breed, elective versus emergency c‐section, litter size (c‐section and total [including those born prior to and via c‐section]), and neonatal survival to discharge. A generalized linear mixed model (univariable and multivariable) was performed to evaluate variables versus neonatal survival. Results: Overall neonatal survival to discharge was 93.1% (447/480); survival was similar between brachycephalic and nonbrachycephalic breeds ( p  = .221, 202/213 [94.8%] brachycephalic survival, 245/267 [91.8%] nonbrachycephalic survival). Puppies delivered via elective c‐section were more likely to survive compared to emergency c‐section ( p  < .001, 238/240 [99.2%] elective survival, 209/240 [87.1%] emergency survival). Puppies delivered in larger c‐section litters were more likely to survive ( p <  .004) compared to smaller litters. Total litter size had no effect on survival. Conclusion: Brachycephalism had no effect on neonatal survival. Puppies delivered via elective c‐section were more likely to survive compared to puppies delivered via emergency c‐section. Clinical significance: Outcomes following c‐section are similar between brachycephalic and nonbrachycephalic breeds. While it is preferable to encourage selective breeding for bitches that are able to whelp naturally, elective c‐section should be considered in bitches at high risk for dystocia to maximize neonatal survival.